In-situ synthesis of Boron Nitride Nanotube reinforced aluminum oxide composites by molecular mixing. Issue 10 (15th May 2021) - Lu, Xiaolong; Dolmetsch, Tyler; Zhang, Cheng; Chen, Yao; Boesl, Benjamin; Agarwal, Arvind
Abstract: Boron Nitride Nanotube (BNNT)/Al2 O3 composite powders were prepared by molecular mixing of aqueous nanotube dispersions and aluminum ions. The composite powder was consolidated by spark plasma sintering where the ceramic phase underwent phase transformation to α-Al2 O3 (amorphous→γ→α) while anchoring molecularly mixed BNNTs. The addition of 1.5 vol% BNNTs reduced the Al2 O3 grain size by 50%, whereas microhardness increased by 22%. With an increasing BNNTs content from 0 to 1.5 vol%, high load (100 N) indentation showed that the residual indention area decreased by 65%, and morphology changed from severely brittle fracture to no visible cracks. Thus the addition of BNNTs leads to simultaneous improvement of strength and toughness of Al2 O3 . Crack bridging, BNNT pull-out, and crack deflection are the prime toughening mechanisms. Grain refinement of the Al2 O3 matrix and effective load sharing is attributed to in-situ and homogeneously dispersed BNNTs, which are chemically bonded with the Al2 O3 matrix at the molecular level.